HEPATOPROTECTIVE ACTIVITY OF LEAF OF METHANOL EXTRACT OF LAURUS NOBILIS.L AGAINST PARACETAMOL INDUCED HEPATOTOXICITY IN RATS - Ravindran, Chandrasekaran Arcot; Murugaiyah, Vikneswaran A/L; Khiang, Peh Kok; Xavior, R. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The present study was conducted to evaluate the hepatoprotective activity of methanol extract of Laurus nobilis against paracetamol induced liver damage in rats. Materials and Methods: The methanol extract of Laurus nobilis (200 mg/kg & 400 mg/kg) was administered orally to the animals with hepatotoxicity induced by paracetamol (400 mg/kg). Silymarin (25mg/kg) was given as reference standard. All the test drugs were administered orally by suspending in 0.5% Carboxy methyl cellulose solution. Results: Paracetamol has enhanced the levels of ALT, AST, ALP and bilirubin, whereas the group receiving high dose (400 mg/kg body weight) methanol extract of Laurus nobilis was effective in protecting the liver against the injury induced by paracetamol in rats than that ofÂ low dose (200mg/kg body weight) treated group. This was evident from a significant reduction in serum enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and bilirubin. Conclusion: It was concluded from the result that the methanol extract of Laurus nobilis acts on the liver as a potent scavenger of free radicals to prevent the toxic effects of paracetamol induced hepatotoxicity in rats. Keywords: Laurus nobilis, ALT, AST, ALP, hepatotoxicity.